The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1007/s15010-012-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infections in long-term care facilities: how to read it?

Abstract: The prevalence of infections in LTCFs needs to be interpreted cautiously, given the effects of seasonality and case-mix variation. Repeated prevalence surveys may be a good start in individual facilities, but the identification of outbreaks requires a continuous surveillance system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24] Most reported UTI as the most common type of infection. 15,16,[19][20][21][22][23] Despite a lower prevalence in our survey compared with overseas surveys, we must interpret the results with caution for a few reasons. First, the difference in survey method, study population, and case definition among these studies may render direct comparison of prevalence inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Most reported UTI as the most common type of infection. 15,16,[19][20][21][22][23] Despite a lower prevalence in our survey compared with overseas surveys, we must interpret the results with caution for a few reasons. First, the difference in survey method, study population, and case definition among these studies may render direct comparison of prevalence inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Infections included in this analysis (Table ) were chosen based on previously published literature on infections commonly encountered in LTC facilities . Codes identified in the infectious and parasitic disease chapter of the Sixth Edition if the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM), were also included in the list .…”
Section: Methodsmentioning
confidence: 99%
“…Despite these limitations, there is substantial information about the types of infections commonly found in LTC settings: urinary tract, lower respiratory tract, skin and soft tissue, and gastrointestinal . Previous literature has found prior hospitalization, indwelling device use, and functional disability to be associated with NH‐associated infections, but no studies have examined whether these risk factors are consistent across different LTC settings or whether they would persist in a larger or national sample.…”
mentioning
confidence: 99%
“…59,[88][89][90][91] Several studies have demonstrated that the most-frequent types of infections found in LTCF residents are pneumonia, UTI, and skin and soft tissue infections. 24,88,92 These three types of infections are also most commonly found in individuals receiving care in hospice and home health settings, 88 although acute gastroenteritis, notably norovirus infections and CDI (the latter discussed earlier) are also commonly found in LTCFs. 93 Long-term care facilities lack many of the opportunities, processes, staffing, and other resources available in acute-care inpatient settings.…”
Section: Unique Diagnostic and Management Challenges Of Treating Gerimentioning
confidence: 99%
“…Infection in LTCF residents is one of many healthcare concerns confronting healthcare providers, administrators, and policy‐makers . Several studies have demonstrated that the most‐frequent types of infections found in LTCF residents are pneumonia, UTI, and skin and soft tissue infections . These three types of infections are also most commonly found in individuals receiving care in hospice and home health settings, although acute gastroenteritis, notably norovirus infections and CDI (the latter discussed earlier) are also commonly found in LTCFs …”
Section: Unique Diagnostic and Management Challenges Of Treating Gerimentioning
confidence: 99%